Folklore and Education: The Kesah Pang Alui in the Interior of West Kalimantan - Syahrani, Agus; Yusriadi, Yusriadi; Asfar, Dedy Ari; Anderbeck, Karl (Al-Hayat: Journal of Islamic Education, 2024)
This study aims to analyze the relationship between folklore and education. What cultural values can be used for educational purposes, and how can they be used? The data is taken from the story of Pang Alui, a folklore of people in the interior of Kapuas Hulu, West Kalimantan. This story is an archive of researchers' oral literature research from 1996 to 1997. Interviews with several people were also conducted to get their views on the values of the folklore for the education of the younger generation. Folklore has a lot of value in learning. There are educational values, among others: persevering, learning and meticulous, cooperation and willingness to share. More than that, folklore is also meaningful in terms of language and cultural information. Given its proximity to society, folklore can serve as a pedagogical resource in an educational environment, both in specialized subjects and integrated into other lessons. This study has implications for the awareness of all parties to pay attention to the existence of folklore in the community; teachers utilize the material, students become closer to cultural heritage, researchers do documentation, and stakeholders maintain the continuity of the literature. This study has important significance in looking back at the relationship between folklore and education, in particular, in reaffirming that folklore must be documented and inherited. The inheritance can be done through educational institutions.